2020
DOI: 10.22271/ortho.2020.v6.i2b.2019
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of arthroscopic rotator cuff repair

Abstract: To improve the clinical outcomes and to detect the significant predictors of outcome of rotator cuff repair, such as age, sex, side, tear size, fixation methods, smoking, and associated pathology have been investigated in the Indian population. Methods: Forty patients (27 male and 13 female) were included in the study who had complete degenerated rotator cuff tear, managed by arthroscopic single or double row repair technique and follow up till one year at a single institution. Postoperatively, patients were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…The study by Vikram and Anshuman observed that 62.5% of patients had only supraspinatus tears and 37.5% of patients had both supra and infraspinatus tears among the 40 recruited patients. The data is in accordance with our study [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study by Vikram and Anshuman observed that 62.5% of patients had only supraspinatus tears and 37.5% of patients had both supra and infraspinatus tears among the 40 recruited patients. The data is in accordance with our study [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…We also observed that 90% of the recruited patients in our study belonged to this age group. Similar to our findings, a study by Vikram and Anshuman (2020) recruited 40 patients with a mean age of 59 years who underwent rotator cuff repair surgery with a single or double-row suture anchor technique [24]. Among the recruited patients, 64% were females and 36% were males.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation